2009
DOI: 10.1113/jphysiol.2009.176206
|View full text |Cite
|
Sign up to set email alerts
|

A Ca2+‐activated Cl conductance in interstitial cells of Cajal linked to slow wave currents and pacemaker activity

Abstract: Interstitial cells of Cajal (ICC) are unique cells that generate electrical pacemaker activity in gastrointestinal (GI) muscles. Many previous studies have attempted to characterize the conductances responsible for pacemaker current and slow waves in the GI tract, but the precise mechanism of electrical rhythmicity is still debated. We used a new transgenic mouse with a bright green fluorescent protein (copGFP) constitutively expressed in ICC to facilitate study of these cells in mixed cell dispersions. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
354
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(373 citation statements)
references
References 42 publications
16
354
1
2
Order By: Relevance
“…2E). Recently, Zhu et al [13] suggested that Ca 2+ -activated Cl À conductance is involved in the pacemaking activity of ICCs, and another recent study confirmed that ICCs express ANO1 in the GI tract [14]. In addition, ANO1 was recently shown to function as a Ca 2+ -activated Cl À channel [15][16][17], and loss or block of ANO1 was found to block electrical slow waves in intact GI muscles [18].…”
Section: Resultsmentioning
confidence: 98%
“…2E). Recently, Zhu et al [13] suggested that Ca 2+ -activated Cl À conductance is involved in the pacemaking activity of ICCs, and another recent study confirmed that ICCs express ANO1 in the GI tract [14]. In addition, ANO1 was recently shown to function as a Ca 2+ -activated Cl À channel [15][16][17], and loss or block of ANO1 was found to block electrical slow waves in intact GI muscles [18].…”
Section: Resultsmentioning
confidence: 98%
“…The pacemaker activity in the murine small intestine is due mainly to periodic activation of nonselective cation channels (NSCCs) (Koh et al, 2002) and we suggested that the electrophysiologi- cal and pharmacological properties of TRPM7 and the NSCCs in ICCs were the same and, therefore, the TRPM7 protein is an essential molecular component of NSCC in ICCs (Kim et al, 2005). Also, Zhu et al (2009) suggested that Ca 2+ -activated Clconductance is also involved in slow wave current in ICC and that ANO1 participates in pacemaker activity. Recently, Chen et al (2010) suggested that the 5-LOX inhibitors, NDGA, AA861 and MK886 reduced the TRPM7 channel activity independent of their effect on 5-LOX activity.…”
Section: Discussionmentioning
confidence: 98%
“…However, the exact action mechanisms need to be investigated. TRPM7 or Ca 2+ -activated Cl -conductance is involved in pacemaking activity in ICCs (Kim et al, 2005;Zhu et al, 2009). To investigate the effects of 5-LOX inhibitors on Ca 2+ -activated Cl -conductance, we overexpressed Ca 2+ -activated Cl -channels in HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations